Plasma proteome profiling discovers novel proteins associated with non‐alcoholic fatty liver disease. Issue 3 (1st March 2019) - Niu, Lili; Geyer, Philipp E; Wewer Albrechtsen, Nicolai J; Gluud, Lise L; Santos, Alberto; Doll, Sophia; Treit, Peter V; Holst, Jens J; Knop, Filip K; Vilsbøll, Tina; Junker, Anders; Sachs, Stephan; et al.
Abstract: Non‐alcoholic fatty liver disease (NAFLD) affects 25% of the population and can progress to cirrhosis with limited treatment options. As the liver secretes most of the blood plasma proteins, liver disease may affect the plasma proteome. Plasma proteome profiling of 48 patients with and without cirrhosis or NAFLD revealed six statistically significantly changing proteins (ALDOB, APOM, LGALS3BP, PIGR, VTN, and AFM), two of which are already linked to liver disease. Polymeric immunoglobulin receptor (PIGR) was significantly elevated in both cohorts by 170% in NAFLD and 298% in cirrhosis and was further validated in mouse models. Furthermore, a global correlation map of clinical and proteomic data strongly associated DPP4, ANPEP, TGFBI, PIGR, and APOE with NAFLD and cirrhosis. The prominent diabetic drug target DPP4 is an aminopeptidase like ANPEP, ENPEP, and LAP3, all of which are up‐regulated in the human or mouse data. Furthermore, ANPEP and TGFBI have potential roles in extracellular matrix remodeling in fibrosis. Thus, plasma proteome profiling can identify potential biomarkers and drug targets in liver disease. Synopsis: Applying Plasma Proteome Profiling to liver disease in different human cohorts associated PIGR and ALDOB and other proteins to non‐alcoholic fatty liver disease. Potential biomarkers were validated in a mouse model. Plasma proteome profiling augmented by Boxcar acquisition identified potential biomarkers of human liver diseases. PIGR and ALDOB are associated with NAFLD, among other novel proteins. DPP4, ANPEP, PIGR, APOE, and TGFBI highly correlate with AST, ALT, GGT and ALP. A mouse NAFLD model recapitulated many of the changes seen in humans. Abstract : Applying Plasma Proteome Profiling to liver disease in different human cohorts associated PIGR and ALDOB and other proteins to non‐alcoholic fatty liver disease. Potential biomarkers were validated in a mouse model.